The assessment of preschool children with ESSENCE symptoms: concordance between parents, preschool teachers and child psychologists - B. M. Gustafsson; M. Sund Levander (BMC, 2024)
Abstract Background It is important to detect children with Early Symptomatic Syndromes Eliciting Neurodevelopmental Clinical Examinations (ESSENCE) in order to implement early intervention and support for the child and family. Standardized instruments for assessment in different contexts of behaviour problems, engagement and psychosocial health obtain an objective picture of the preschool child's mental health. Aim To explore and compare parents', preschool teachers' and child health care psychologists' assessment of behaviour, everyday function, engagement, social interaction and psychosocial health in children with ESSENCE symptoms. Method Parents of 152 children (114 boys and 38 girls, 4.5 ± 1 years) with ESSENCE symptoms, 155 preschool teachers and 8 child psychologists participated. Parents and preschool teachers assessed externalizing and internalizing behavioural problems using the Strengths and Difficulties Questionnaire (SDQ), including the SDQ supplement for assessing the impact of behavioral problems on daily function. Preschool teachers also assessed engagement and social interaction using the Children's Engagement Questionnaire (CEQ), and the child psychologists assessed psychosocial health with the Child Psychosocial Health Assessment (LillaLAPS) and template in conversations with parents of children with neurodevelopmental problems. Results Parents', preschool teachers' and child psychologists' assessment of the child's ESSENCE symptoms overall agreed. Both parents and preschool teachers see a strength in the child's social abilities. Differences in mean values show that parents assess more conduct, emotional symptoms and problems in daily life and more social skills, compared to the preschool teachers rating more peer problems. Conclusion It is important to consider different contexts to identify the child's need for support in everyday life. Expanded use of validated screening instruments in clinical practice would promote detection of children not already identified as exhibiting neurodevelopmental problems.